Synthesis of 3,5-Diaryl-1-Pyridoyl Pyrazoles - Tayde, V.B.; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some of the new 3,5-diaryl pyrazoles have been synthesized by a novelmethod. 2-Aroyl acetophenones with isoniazide in alcohol medium containinga little piperidine produces 3,5-diaryl-1-pyridoyl pyrazoles. Structuresof these compounds have been established by spectral analysis. (lR,UV and NMR).